2009
DOI: 10.1117/12.820235
|View full text |Cite
|
Sign up to set email alerts
|

Directional analysis and filtering for dust storm detection in NOAA-AVHRR imagery

Abstract: I take this opportunity to express my sincere thanks to my advisor, Dr. Sergio. D. Cabrera, for providing me this opportunity. I appreciate his guidance and support without which this thesis could not be done. I would like to acknowledge the support received from the Texas Instruments Foundation Endowed Scholarship Program. I would extend my heartfelt gratitude to Mr. Vikram Jayaram for sparing his valuable time, guiding me at every stage and for his continuous encouragement and support. I would also like to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…To assure that the selected images demonstrate dust events, the Brightness Temperature Difference (BTD) procedure was applied (Janugani et al, 2009):…”
Section: Remote Sensing Monitoring Of Dust Storms In the Aral Region mentioning
confidence: 99%
See 3 more Smart Citations
“…To assure that the selected images demonstrate dust events, the Brightness Temperature Difference (BTD) procedure was applied (Janugani et al, 2009):…”
Section: Remote Sensing Monitoring Of Dust Storms In the Aral Region mentioning
confidence: 99%
“…Recent studies have demonstrated the efficiency of using thermal bands for monitoring dust aerosol outbreaks (Hu et al, 2008). An effective method for detecting and differentiating dust from clouds using satellite remote sensing has been the brightness temperature difference (BTD) of NOAA/AVHRR channel 4 and channel 5 (Chavez et al, 2002;Janugani et al, 2009;Tsolmon et al, 2008;Prospero, 1999). The BTD of the two bands can distinguish not only a dust storm but also the density of dust and sand in the moving mass (Tsolmon et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, in principle, the severity of dust storms, the areas they affect and changes in intensities can be monitored using appropriate remotely sensed images [4]. Many researchers have proposed methods aiming to distinguish dust storms from clouds, ground and water surfaces using images from instrument such as MERIS [5], TOMS [8], SeaWiFS [9], GOES [10] and MODIS (Terra and Aqua) [1], [2], [4], [5], [11] and those on the satellites NOAA-AVHRR [12], Landsat and GMS [13]. In this study we have concentrated on MODIS (Moderate Resolution Imaging Spectroradiometers) data because it includes 36 spectral bands, which potentially provides more opportunities for developing techniques for the detection of dust storms than the data from other instruments.…”
mentioning
confidence: 99%